Case report Multiple mononeuropathy due to vasculitis associated with anticardiolipin antibodies: a case report - Jeruc, Jera; Popović, Mara; Vizjak, Alenka; Jurčić, Vesna; Lestan, Boris; Ferluga, Dušan (Folia Neuropathologica, 2006)
This report illustrates a case of peripheral nerve vasculitis associated with elevated anticardiolipin antibodies. A 49-year-old female with a history of seven spontaneous abortions initially complained of pain and numbness in her right calf that later spread to the left foot and ankle. Over the next few months, she developed a Raynaud phenomenon and livedo reticularis. Clinical examination revealed signs of multiple mononeuropathy. Right sural nerve biopsy performed two months after the beginning of the disease revealed active necrotizing arteritis of the epineural arteries with transmural inflammatory infiltrate and thrombosis. Vasculitis is a rare finding in sural nerve biopsies, usually in patients with systemic vasculits or autoimmune connective tissue diseases. However, vasculitis restricted to the peripheral nerves has also been described. Our patient had no clinical or laboratory features of any autoimmune disorder and also no signs of systemic vasculitis. We discuss the potential role of anticardiolipin antibodies in the pathogenesis of vasculitis.